Proceedings of the International Workshop on the New Applications of Nuclear Fission : (World Scientific, 2004)
This book covers new experimental and theoretical studies that focus on the modern developments of nuclear fission, aiming at various applications in a wide range of fields and bringing together scientists working in different fields related to nuclear fission. The following topics are dealt with: radioactive beam facilities based on nuclear fission; nuclear waste transmutations and the future accelerator-driven system; fission and spallation nuclear data and modeling; experimental and theoretical advances in the study of nuclear fission; fusion reactions and decay modes of superheavy nuclei; stability against fission and many-body systems; superasymmetric and multicluster fission.